2016
DOI: 10.1007/978-1-4939-6728-5_10
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Isolation of Extracellular Vesicles and Characterization of Exosomes from Brain Extracellular Space

Abstract: Extracellular vesicles (EV), including exosomes, secreted vesicles of endocytic origin, and microvesicles derived from the plasma membrane, have been widely isolated and characterized from conditioned culture media and bodily fluids. The difficulty in isolating EV from tissues, however, has hindered their study in vivo. Here, we describe a novel method designed to isolate EV and characterize exosomes from the extracellular space of brain tissues. The purification of EV is achieved by gentle dissociation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 16 publications
1
68
0
1
Order By: Relevance
“…Brain EVs were isolated as previously described [40, 41] from DS patients and age-matched normal controls (Table 1), and from the right hemibrain of 3-, 8-, 12- and 24-month-old Ts2 mice and 2N littermates. Separation of the EVs on a sucrose gradient resulted in 7 fractions, from a, the least dense, to g, the densest fraction, and Western-blot analysis showed that fractions with densities higher than 1.07 and lower than 1.17 (fractions b, c and d) were immunoreactive to Flotillin-1 and Flotillin-2, lipid raft proteins found in EVs, and established exosomal markers (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Brain EVs were isolated as previously described [40, 41] from DS patients and age-matched normal controls (Table 1), and from the right hemibrain of 3-, 8-, 12- and 24-month-old Ts2 mice and 2N littermates. Separation of the EVs on a sucrose gradient resulted in 7 fractions, from a, the least dense, to g, the densest fraction, and Western-blot analysis showed that fractions with densities higher than 1.07 and lower than 1.17 (fractions b, c and d) were immunoreactive to Flotillin-1 and Flotillin-2, lipid raft proteins found in EVs, and established exosomal markers (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In each experiment, EVs were simultaneously isolated from a brain of either a DS patient or a Ts2 mouse and from an age-matched 2N control. Brain EVs were isolated and purified as we have previously described [40, 41]. Briefly, frozen brain tissues were treated with 20 units/ml papain (Worthington, Lakewood, NJ) in Hibernate A solution (HA, 3.5 ml/sample; BrainBits, Springfield, IL) for 15 min at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the role of Alix, an accessory ESCRT-associated protein, is more complex (Bissig & Gruenberg, 2014). Although it is commonly found in brain exosome preparations (Perez-Gonzalez et al, 2017), its contribution to ILVs formation depends on the cell type (Baietti et al, 2012;Colombo et al, 2013), can be dispensable for exosome biogenesis (Trajkovic et al, 2008), and it does not correlate with TSG101 levels in the brain (Peng et al, 2019). Moreover, in contrast to TSG101, Alix downregulation does not alter MVBs functionality and lysosomal sorting (Bowers et al, 2006;Luyet et al, 2008), suggesting that it may act more upstream in the pathway, probably at the level of the cargo loading into MVBs (Bissig & Gruenberg, 2014).…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Extracellular vesicles (EVs) enriched with exosomes were isolated and purified from frozen mouse hemibrains, as described by Perez-Gonzalez et al (31). In brief, frozen hemibrains were treated with 20 U/ml papain (Worthington, Lakewood, NJ, USA) in Hibernate A solution (HA, 3.5 ml/sample; BrainBits, Springfield, IL, USA) for 15 min at 37°C.…”
Section: Extracellular Vesicle Isolationmentioning
confidence: 99%